2014
DOI: 10.1159/000368556
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells from Female Donors Enhance Breast Cancer Cell Proliferation in vitro

Abstract: The interplay between tumor stroma and breast cancer cells (BCCs) is thought to play a significant role in breast cancer. The current knowledge of human mesenchymal stromal cell (MSC) and BCC interaction is contradictory, and the donor sex issue is not addressed at all. We hypothesized that donor sex could have an effect on proliferation of MSCs or BCCs in co-culture in vitro. Three estrogen receptor-negative BCC lines, 19 primary human MSCs and breast tissue-derived fibroblasts from 4 donors were used. MSCs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Moreover, Fibroblast/cancer cell metabolic cooperation MI Koukourakis et al mesenchymal stromal cells have been shown to stimulate breast cancer cell growth, a result that, at least in part, is related to soluble factors excreted by the mesenchymal cells. 15 Partial silencing of PDH in fibroblasts did not affect the stimulatory effect of cancer cells on fibroblast cell proliferation. This, however, was shown to be a result of abrogation of the silencing effect by the lactate produced by cancer cells (lactate induces PDH in fibroblasts treated with siPDH).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, Fibroblast/cancer cell metabolic cooperation MI Koukourakis et al mesenchymal stromal cells have been shown to stimulate breast cancer cell growth, a result that, at least in part, is related to soluble factors excreted by the mesenchymal cells. 15 Partial silencing of PDH in fibroblasts did not affect the stimulatory effect of cancer cells on fibroblast cell proliferation. This, however, was shown to be a result of abrogation of the silencing effect by the lactate produced by cancer cells (lactate induces PDH in fibroblasts treated with siPDH).…”
Section: Discussionmentioning
confidence: 94%
“…These discs contain all of the cell types and bone matrix that are involved in breast cancer colonisation and growth in this environment. Many in vitro models have tried to recapitulate these interactions between bone cells and tumour cells including co-culture of breast cancer cells with fibroblasts [22,23], mesenchymal stromal cells [24] osteoclasts [25], osteoblasts or a mixture of these cell types [26]. When cultured on plastic these models lack the 3D space that is critical in determining cancer cell function (reviewed in [27]).…”
Section: Tumour Cells In Moving Culturementioning
confidence: 99%
“… [ 25 ] Bone Marrow M:7 F:12 Breast cancer cells proliferate increasingly when MSCs from female donors are involved. [ 31 ] Bone Marrow M:6 F:3 Female BM-MSCs’ sphingolipidome consisted of 88.35% ceramide, and 10.18% sphingomyelin. On the other hand, male BM-MSCs’ sphingolipidome included 54% ceramide, and 44.53% sphingomyelin.…”
Section: The Impact Of Donor Sex On Msc Heterogeneity and Potencymentioning
confidence: 99%